Circulating levels of monocyte chemoattractant protein-1 and interleukin-7 in women who have undergone bilateral salpingo-oophorectomy - Tani, Anna (Dove Medical Press, 2013)
PURPOSE: The aim of the study reported here was to determine the effect of surgical menopause by bilateral salpingo-oophorectomy (BSO) on circulating levels of cytokines and chemokines related to the pathogenesis of atherosclerosis. PATIENTS AND METHODS: A total of 110 women were recruited for this study from the outpatient clinic of our facility. We divided the women into three groups: 1) women with a regular menstrual cycle, 2) women in whom less than 5 years had passed since their BSO, and 3) women in whom 5 years or more had passed since their BSO. Concentrations of nine cytokines and chemokines in serum were measured. RESULTS: The serum monocyte chemoattractant protein-1 (MCP-1) level in women in whom less than 5 years had passed since their BSO was significantly higher than in women with a regular menstrual cycle (P<0.05). There were significant differences in serum interleukin (IL)-7 among the three groups (P=0.035). MCP-1 showed a significant positive correlation (r=0.320, P=0.008) with follicle-stimulating hormone in women with a regular menstrual cycle and in women in whom less than 5 years had passed since their BSO. CONCLUSION: A hypoestrogenic state due to BSO induced changes in MCP-1 and IL-7 levels. MCP-1 level showed a significant increase in the early period after BSO, while IL-7 level showed a significant decrease in the late period after BSO.